ETHNOGRAPHIC NOTES FOR THE DEVELOPMENT OF FILES UNDER THE LOOK OF CRITICAL HERITAGE - Andrade, Pablo; Martínez P., María Angélica (Revista de Historia Social y de las Mentalidades, 2024)
This article studies, from a descriptive perspective, the organization and finality of three different archives whose purpose is to preserve the memory of chores of the political-social and artistic world of the country. From these three case studies framed as a single unit of analysis, an ethnographic strategy is developed that, on the one hand, allows the visualization of the main problems faced by the documentation centers in both the rescue processes, registration, documentation and conservation of its funds and collections, and on the other, it allows to observe that the concept of value of the documents is split from the technical field that characterizes the archival work, defining this, for now, in the potential linkage of its memories with communities, audiences or users. In summary, a reflection is proposed that urges the archive to position itself not only as a repository of documents that arise in an earlier time to speak precisely of that past, but to understand it as a complex center of a memory of the past that makes sense in the Present.